Crystal structure of bis(1,8-dibenzoyl-7-methoxynaphthalen-2-yl)terephthalate: Terephthalate phenylene moiety acts as bidentate hydrogen acceptor of bidirectional C-H···π non-classical hydrogen bonds - Iida, Kikuko; Sakamoto, Rei; Li, Kun; Kobayashi, Miyuki; Iitsuka, Hiroaki; Yonezawa, Noriyuki; Okamoto, Akiko (European Journal of Chemistry, 2021)
The title compound lies about a crystallographic inversion centre located at the terephthalate moiety. The two peri-benzoylnaphthalene units having atrope chirality are also situated centrosymmetrically. In the two peri-benzoylnaphthalene moieties, two benzoyl groups are substituted at 1 and 8 carbons of the naphthalene ring in anti-orientation. Then two absolute configurations of peri-benzoylnaphthalene moieties are consequently assigned as complementary to each other, i.e., one unit has R,R-configuration and the other S,S-one, respectively. The two benzoyl groups in peri-benzoylnaphthalene moiety and the terephthalate phenylene ring are non-coplanarly located against the naphthalene ring. The dihedral angles of each benzene ring of two benzoyl groups and terephthalate unit with the naphthalene ring are 73.73 and 75.96, and 71.79°. In molecular packing, several kinds of weak interactions are responsible to induce three-dimensional molecular network. Especially, the synergetic effect realized through the bidentate hydrogen acceptor function in bidirectional C-H···π non-classical hydrogen bonds by the terephthalate phenylene ring moiety plausibly plays the determining role.